Development and test of a self-centering fluidic viscous damper - Zhu, Ruizhao; Guo, Tong; Mwangilwa, Frank (Advances in structural engineering, 2020)
This research presents a novel self-centering fluidic viscous damper that incorporates preloaded ring springs to offer self-centering capability and a fluidic viscous damper for energy dissipation. A full-scale self-centering fluidic viscous damper was developed and subjected to low-cyclic reversed loading tests. The test results show the self-centering fluidic viscous damper has both displacement-dependent and velocity-dependent hysteric responses with self-centering capability. Fatigue tests further show that the self-centering fluidic viscous damper maintains a stable hysteretic response under reversed loading. An analytical model and a numerical model are developed for the proposed self-centering fluidic viscous damper and analyzed. Comparisons of test results and the numerical and analytical models show similar hysteric responses, thereby validating the accuracy of the numerical and analytical models to simulate the behavior of the proposed damper.